2020
DOI: 10.15537/smj.2020.11.25497
|View full text |Cite
|
Sign up to set email alerts
|

Association between preeclampsia and prostasin polymorphism in Pakistani females

Abstract: Objectives: To investigate the relationship between a prostasin gene variations and the development of preeclampsia in a Pakistani female population. Methods: This was a case-control study carried out at University of Karachi, Karachi, Pakistan between May 2018 and 2019. A single nucleotide polymorphism (SNP) at rs12597511 locus was examined with polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) analyses in 76 preeclamptic and 74 normot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…They reported that the C genotype of (rs12597511) was significant in PE patients. Therefore, the C allele polymorph might be a potential risk to PE pathogenesis [ 118 ].…”
Section: Genetic Polymorphism and Its Association With Pre-eclampsiamentioning
confidence: 99%
“…They reported that the C genotype of (rs12597511) was significant in PE patients. Therefore, the C allele polymorph might be a potential risk to PE pathogenesis [ 118 ].…”
Section: Genetic Polymorphism and Its Association With Pre-eclampsiamentioning
confidence: 99%
“…A pré-eclâmpsia (PE) é um distúrbio peculiar do período gestacional, sendo geralmente caracterizada por hipertensão (> 140/90 mmHg) e proteinúria (> 300 mg/24 horas) desenvolvido após 20 semanas de gestação, a PE e a eclâmpsia são uma das quatro categorias associadas aos distúrbios hipertensivos da gravidez (TANG et al, 2021). Uma vez que, esses distúrbios, incluindo hipertensão crônica, com ou sem PE/eclâmpsia sobreposta, hipertensão gestacional, síndrome HELLP, PE com ou sem características graves ou eclâmpsia apresentam um risco significativo de morbidade tanto para a mãe quanto para o feto, a cada ano a PE causa mais de 500.000 mortes fetais e 70.000 maternas em todo o mundo (EJAZ et al, 2020). Embora cuidados pré-natais adequados com observação atenta para detectar sinais de PE e parto imediato para reduzir ou evitar efeitos adversos tenham produzido redução da morbidade e mortalidade, eles ainda existem (LUGER; KIGHT, 2021).…”
Section: Introductionunclassified